Accuracy of stroke volume variation and pulse pressure variation in predicting fluid responsiveness undergoing one-lung ventilation during thoracic surgery: a systematic review and meta-analysis - Wang, Cuicui; Feng, Zhe; Cai, Jinchen; Duan, Mingda; Li, Huan; Dai, Ziqing; Lv, Hao; Xu, Zhe; Wang, Henglin; Chen, Yu (Annals of translational medicine, 2023)
Stroke volume variation (SVV) and pulse pressure variation (PPV) are based on the interaction between the heart and lungs during mechanical ventilation. However, debate continues as to whether SVV and PPV can accurately predict fluid responsiveness during the one-lung ventilation (OLV). We therefore undertook a systematic review and meta-analysis of clinical trials that investigated the diagnostic value of SVV and PPV in predicting fluid responsiveness undergoing OLV during thoracic surgery. The MEDLINE, EMBASE, WANFANG, and CENTRAL databases were systematically searched for studies on the use of SVV and/or PPV in patients undergoing OLV from 2010 to 2021. Heterogeneity was assessed using I statistics. The funnel diagram analysis was used to test publication bias. A fixed-effects model was used to calculate the pooled values of sensitivity, specificity, the diagnostic odds ratio (DOR), and the relevant 95% confidence intervals (95% CIs). The summary receiver operating characteristic (SROC) curves were estimated, and the areas under the SROC curve were calculated. In total nine studies, comprising 452 patients were ultimately included in this meta-analysis, including 217 (48%) responders and 235 (52%) nonresponders. After combining the correlation coefficients, a slight heterogeneity was found between SVV and PPV in these selected studies (I =19.7%, I =15.3%), and the funnel diagram also showed that the P values of SVV and PPV were 0.33 and 0.26. After the pooled analysis, the respective sensitivity of SVV and PPV in predicting fluid responsiveness was 0.66 and 0.61, the specificity was 0.62 and 0.53, the positive likelihood ratios were 1.7 and 1.3, the negative likelihood ratios were 0.55 and 0.74, and the DORs were 3 and 2. The areas under the SROC curve of SVV and PPV were 0.68 and 0.60, respectively, according to STATA SE16 software, and the combined areas under the receiver operating characteristic (ROC) curve of SVV and PPV were 0.681 and 0.604, respectively, according to MedCalc19.0.4 software. Current evidence suggests that SVV and PPV are not suitable for guiding intraoperative fluid therapy due to their poor ability to predict fluid responsiveness in patients undergoing OLV, and we need a better indicator instead.